ОСОБЛИВОСТІ МІЖОСОБИСТІСНИХ СТОСУНКІВ ТА КОМУНІКАТИВНИХ УСТАНОВОК ДЕПРЕСИВНИХ ОСІБ - Анна Вовк (International Journal of Innovative Technologies in Social Science, 2020)
A comparison and analysis of features of dialogue communication, perceptive and іnteractive competence, relationship disharmony and needs in interpersonal relations, loneliness, emotional barriers in communication for persons with different levels of depression manifestations are made. Interconnections between depression index and dialogue ability in communication, perceptive and іnteractive competence, relationship disharmony (tension, alienation, aggressiveness, conflicts) and needs in interpersonal relations (acceptance, control, inclusion, closeness), loneliness experience, and emotional barriers in a communication are analyzed and interpreted.Depressive state is strongly connected with the need of control of social surrounding, rigidity of negative emotional state with lack of control upon it and loneliness experience. Somatic component of depressive state, which often is called to hide depressive emotions provides social and psychological adaptation of depressive person, helps to take control of social surrounding and legalize the need of social support (however its amount and quality is still not satisfying).